Deploying the post-colonial predicaments of researching on/with 'Asia' in education: a standpoint from a rich peripheral country. Issue 1 (2nd January 2016) - Takayama, Keita
Abstract : Against the current infatuation with Asia in Australian education, this article rearticulates the notion of 'Asia literacy' to explore new ways of researching on/with/through Asia. Drawing on the post-colonial critique of Western social science knowledge, I first demonstrate the problematic nature of Australian knowledge production on and with Asia in social science and education. And yet, I also highlight the contribution that Australian scholars have made to decolonizing knowledge work, with particular attention to their critique of internationalization of cultural studies in the 1990s. In so doing, I identify the particular epistemic standpoint of Australian scholarship, which has emerged out of its ambivalent location in the global politics of academic knowledge production. Then, I identify three types of engagement by Asian researchers with Western knowledge. Situating Australian education scholarship among them, I explore what 'Asia literate' education research might look like from the vantage point of Australia.